Relationship Between Pregnant Women's Knowledge and Compliance in Consumption of Feed Tablets at PMB Novida Efrianti - Harahap, Wahyuni; Bachruddin, Shella; Harahap, Ziadatun Amini; Siregar, Mislaini Barkah; Lubis , Ayu Ulfah Nur (International Journal of Public Health Excellence (IJPHE), 2025)
Iron plays a crucial role in the body, primarily in the formation of hemoglobin, which transports oxygen in red blood cells. It is especially vital for pregnant women, as sufficient iron is necessary for fetal development. In Indonesia, only 51% of pregnant women receive the recommended 90 Fe tablets during pregnancy, and compliance with consumption is alarmingly low at 37.7%. Data reveals that 48.9% of pregnant women suffer from anemia, with 84.2% of these cases occurring in the 15-24 age group (Indonesian Health Profile, 2021). This study aimed to explore the relationship between maternal knowledge and compliance with Fe tablet consumption at PMB Novi, Panyabungan District, Mandailing Natal Regency. Utilizing a descriptive analytical approach and quantitative methods, the study surveyed 33 pregnant women through total sampling. The results indicated a significant relationship, with a p-value of 0.001 (p < 0.05), leading to the rejection of the null hypothesis. This implies that better maternal knowledge correlates with higher compliance in Fe tablet consumption. It is recommended that pregnant women actively seek information on the benefits and proper consumption of Fe tablets to reduce anemia risk. Additionally, health workers should enhance community education regarding maternal health, emphasizing the importance of iron during pregnancy and the advantages of Fe tablet consumption to combat iron deficiency effectively.